Universal vs Risk Factor Screening for Methicillin-Resistant Staphylococcus aureus in a Large Multicenter Tertiary Care Facility in Canada. (16th October 2015) - Roth, V. R.; Longpre, T.; Taljaard, M.; Coyle, D.; Suh, K. N.; Muldoon, K. A.; Ramotar, K.; Forster, A.
Abstract : OBJECTIVE: To assess the clinical effectiveness of a universal screening program compared with a risk factor–based program in reducing the rates of nosocomial methicillin-resistant Staphylococcus aureus (MRSA) among admitted patients at the Ottawa Hospital. DESIGN: Quasi-experimental study. SETTING: Ottawa Hospital, a multicenter tertiary care facility with 3 main campuses, approximately 47, 000 admissions per year, and 1, 200 beds. METHODS: From January 1, 2006 through December 31, 2007 (24 months), admitted patients underwent risk factor–based MRSA screening. From January 1, 2008 through August 31, 2009 (20 months), all patients admitted underwent universal MRSA screening. To measure the effectiveness of this intervention, segmented regression modeling was used to examine monthly nosocomial MRSA incidence rates per 100, 000 patient-days before and during the intervention period. To assess secular trends, nosocomial Clostridium difficile infection, mupirocin prescriptions, and regional MRSA rates were investigated as controls. RESULTS: The nosocomial MRSA incidence rate was 46.79 cases per 100, 000 patient-days, with no significant differences before and after intervention. The MRSA detection rate per 1, 000 admissions increased from 9.8 during risk factor–based screening to 26.2 during universal screening. A total of 644 new nosocomial MRSA cases were observed in 1, 448, 488 patient-days, 323 during risk factor–based screening and 321 during universal screening. Secular trends in C. difficile infection rates and mupirocin prescriptions remained stable after the intervention whereas population-level MRSA rates decreased. CONCLUSION: At Ottawa Hospital, the introduction of universal MRSA admission screening did not significantly affect the rates of nosocomial MRSA compared with risk factor–based screening. Infect. Control Hosp. Epidemiol. 2015;37(1):41–48